2021
DOI: 10.3390/v13030447
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of SARS-CoV-2 in Second Trimester Associated with Severe Neonatal Pathology

Abstract: The effects of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in women on the gestation course and the health of the fetus, particularly in the first and second trimesters, remain very poorly explored. This report describes a case in which the normal development of pregnancy was complicated immediately after the patient had experienced Coronavirus disease 2019 (COVID-19) at the 21st week of gestation. Specific conditions included critical blood flow in the fetal umbilical artery, fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 35 publications
2
38
0
4
Order By: Relevance
“…Moreover, further research and observations of pregnant women and their children with the virus are needed to assess further long-lasting clinical implications which can appear in offspring. Furthermore, more assessment should be made regarding the rates of vertical transmission in the early trimester of pregnancy and the potential risk for consequent fetal morbidity and mortality [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 148 , 149 , 150 , 151 ]. To date, research is underway to check whether the SARS-CoV-2 virus can be transmitted from mother to fetus.…”
Section: Covid 19—placentamentioning
confidence: 99%
“…Moreover, further research and observations of pregnant women and their children with the virus are needed to assess further long-lasting clinical implications which can appear in offspring. Furthermore, more assessment should be made regarding the rates of vertical transmission in the early trimester of pregnancy and the potential risk for consequent fetal morbidity and mortality [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 148 , 149 , 150 , 151 ]. To date, research is underway to check whether the SARS-CoV-2 virus can be transmitted from mother to fetus.…”
Section: Covid 19—placentamentioning
confidence: 99%
“…A small cohort study performed in women infected during late pregnancy found that known risk factors for COVID-19 severity in the general population, such as obesity, increased the need of a premature C-section to alleviate respiratory difficulty ( Lokken et al, 2020 ). Fetal growth restrictions ( Sukhikh et al, 2021 ), low birth weight of at-term babies ( Patanè et al, 2020 ) and occasional miscarriages and stillbirths have also been reported following COVID-19 diagnosis in pregnant patients ( Baud et al, 2020 ; Sukhikh et al, 2021 ). However, in other cohorts no increased risk of premature delivery or impaired fetal growth were described ( Santana and Luis, 2021 ).…”
Section: Clinical Outcomes Of Sars-cov-2 During Pregnancy and Evidence Of Vertical Transmissionmentioning
confidence: 99%
“…Recent reports have shown that the two known receptors for SARS-CoV-2, angiotensin-converting enzyme (ACE2) and transmembrane protease serine 2, are widely expressed in the placenta and in the maternal-fetal interface (M. Li et al, 2020 ), suggesting that, as with any respiratory virus, mother-to-child transmission of SARS-CoV-2 could occur. Accordingly, some case studies have demonstrated the presence of SARS-CoV-2 genome in placentas from women infected during the second and third trimester of pregnancy ( Hosier et al, 2020 ; Patanè et al, 2020 ; Sukhikh et al, 2021 ), with increased placental infiltration of inflammatory cells, mostly phagocytic cells ( Kirtsman et al, 2020 ; Schoenmakers et al, 2020 ). In one of these cases, an uneventful and healthy pregnancy was complicated immediately after the patient acquired COVID-19 at 21 weeks of pregnancy.…”
Section: Clinical Outcomes Of Sars-cov-2 During Pregnancy and Evidence Of Vertical Transmissionmentioning
confidence: 99%
See 2 more Smart Citations